2004
DOI: 10.1152/jn.00946.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spastic Long-Lasting Reflexes in the Awake Rat After Sacral Spinal Cord Injury

Abstract: Spastic long-lasting reflexes in the awake rat after sacral spinal cord injury. J Neurophysiol 91: 2247-2258, 2004; 10.1152/jn.00946.2003. Following chronic sacral spinal cord transection in rats the affected tail muscles exhibit marked spasticity, with characteristic long-lasting tail spasms evoked by mild stimulation. The purpose of the present paper was to characterize the long-lasting reflex seen in tail muscles in response to electrical stimulation of the tail nerves in the awake spastic rat, including i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 42 publications
8
116
0
2
Order By: Relevance
“…Shortly after the injury, the excitability of the spinal cord decreases because this excitatory influence of the brainstem on motoneurons is lost. However, motoneurons slowly recover the capacity to generate PICs, which are, in large part, responsible for longlasting reflexes and spasms (49,50). Both 5-HT 2B Rs and 5-HT 2C Rs, but not 5-HT 2A Rs, are involved in this up-regulation of PICs (44).…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after the injury, the excitability of the spinal cord decreases because this excitatory influence of the brainstem on motoneurons is lost. However, motoneurons slowly recover the capacity to generate PICs, which are, in large part, responsible for longlasting reflexes and spasms (49,50). Both 5-HT 2B Rs and 5-HT 2C Rs, but not 5-HT 2A Rs, are involved in this up-regulation of PICs (44).…”
Section: Discussionmentioning
confidence: 99%
“…3) due to hip movement and/or to the stimulus (Nickolls et al, 2004). Nonetheless, spasms have also been attributed to slowly activating voltagedependent persistent inward currents that enable motoneurons to produce prolonged discharges in response to brief inputs Bennett et al, 2004), which in turn are under control of descending monoaminergic systems that are impaired in people with a SCI.…”
Section: On the Spasms Initiated By The Hip Movement And The Involvedmentioning
confidence: 99%
“…However, in humans and in some animal models, considerable neuromuscular activity sometimes develops after SCI in the form of spasticity, a syndrome that includes hyperreflexia, hypertonus, and long-lasting spasms (Bennett et al 2004;Fujimori et al 1968;Heckman 1994;Kuhn and Macht 1948;Lance and Burke 1974;Ritz et al 1992;Taylor et al 1997). Furthermore, preservation of slow (Hidler et al 2002;Thomas and Ross 1997;Zijdewind and Thomas 2003) and fatigue-resistant (Hartkopp et al 2003) muscle contractile properties has been observed in conjunction with spasticity after SCI in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that after sacral spinal cord transection, rats develop a pronounced spastic syndrome in the segmental muscles of the tail over a period of months (chronic spinal rats) (Bennett et al 1999(Bennett et al , 2001(Bennett et al , 2004. This spasticity is associated with large muscle spasms lasting many seconds that are evoked by brief, normally innocuous sensory inputs to the tail, such as brushing of the tail on the cage bedding during walking; further, there is ongoing spontaneous EMG activity in the muscles lasting for hours at a time (Bennett et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation